Strangers on the shore early coastal contacts in Australia - Veth, Peter Marius; Sutton, Peter, 1946-; Neale, Margo (National Museum of Australia Press, 2008)
"Contacts between Indigenous Australians and outsiders - Macassans, Portuguese, Dutch, English, French, Americans and others - are known to have occurred for 400 years. This book explores these diverse, subtle, dynamic and volatile first encounters from Indigenous and non-Indigenous perspectives. It also looks at the myriad elements of these cross-cultural exchanges, which resulted in profound outcomes for the First Australians. Strangers on the Shore: A Conference on Early Coastal Contacts with Australia was a landmark conference held at the National Museum of Australia on 30-31 March 2006"--Provided by publisher.